Social Boundaries and Marital Assimilation: Interpreting Trends in Racial and Ethnic Intermarriage - Qian, Zhenchao; Lichter, Daniel T. (American Sociological Review, 2007)
Interracial/interethnic marriage in America is a barometer of racial/ethnic relations and intergroup social distance. Using data from the 5-percent Public Use Microdata Sample of the 1990 and 2000 censuses, we interpret trends in intermarriage in light of new assimilation theory, recent changes in racial classification, and rapid demographic changes in American society. Our results indicate that changes in marital assimilation have taken on momentum of their own; that is, America's growing biracial population has fueled the growth of interracial marriages with whites. Analyses also shed new light on the effects of rapid immigration, rising cohabitation, and educational upgrading on intermarriage patterns, and yield both continuities and departures from the past. Historic patterns of racial/ethnic differences in intermarriage persist—Hispanics and American Indians are most likely to marry whites, followed closely by Asian Americans. African Americans are least likely to marry whites. Yet, the 1990s brought significant increases in intermarriage between blacks and whites; large increases in cohabitation did not offset the growth of racially-mixed marriages. The past decade also ushered in unprecedented declines in intermarriage with whites and large increases in marriage between native- and foreign-born co-ethnics among Hispanics and Asian Americans. The role of educational attainment in the out-marriage patterns of Hispanics and Asian Americans was also reinforced. Any evidence of differential growth in African American-white marriages among the highly educated African American population was weak. If intermarriage is our guide, any shifting, blurring, or crossing of racial/ethnic boundaries represent uncommonly weak mechanisms for breaking down existing racial barriers to black-white union formation.